The genetic basis of asymptomatic codon 8 frame‐shift (HBB:c25_26delAA) β0‐thalassaemia homozygotes. (13th January 2016) - Jiang, Zhihua; Luo, Hong‐yuan; Huang, Shengwen; Farrell, John J.; Davis, Lance; Théberge, Roger; Benson, Katherine A.; Riolueang, Suchada; Viprakasit, Vip; Al‐Allawi, Nasir A.S.; Ünal, Sule; Gümrük, Fatma; et al.
Summary: Two 21‐year old dizygotic twin men of Iraqi descent were homozygous for HBB codon 8, deletion of two nucleotides (–AA) frame‐shift β 0 ‐thalassaemia mutation (FSC8; HBB :c25_26delAA). Both were clinically well, had splenomegaly, and were never transfused. They had mild microcytic anaemia (Hb 120‐130 g/l) and 98% of their haemoglobin was fetal haemoglobin (HbF). Both were carriers of Hph α‐thalassaemia mutation. On the three major HbF quantitative trait loci (QTL), the twins were homozygous for G>A HBG2 Xmn1 site at single nucleotide polymorphism (SNP) rs7482144, homozygous for 3‐bp deletion HBS1L‐MYB intergenic polymorphism (HMIP) at rs66650371, and heterozygous for the A>C BCL11A intron 2 polymorphism at rs766432. These findings were compared with those found in 22 other FSC8 homozygote patients: four presented with thalassaemia intermedia phenotype, and 18 were transfusion dependent. The inheritance of homozygosity for HMIP 3‐bp deletion at rs66650371 and heterozygosity for Hph α‐thalassaemia mutation was found in the twins and not found in any of the other 22 patients. Further studies are needed to uncover likely additional genetic variants that could contribute to the exceptionally high HbF levels and mild phenotype in these twins.